Oyster and Pyramidella Shells as Heterogeneous Catalysts for the Microwave-Assisted Biodiesel Production from Jatropha curcas Oil - Achanai Buasri; Tidarat Rattanapan; Chalida Boonrin; Chosita Wechayan; Vorrada Loryuenyong (Journal of Chemistry)
Microwave-assisted biodiesel production via transesterification of Jatropha curcas oil with methanol using solid oxide catalyst derived from waste shells of oyster and Pyramidella was studied. The shells were calcined at 900°C for 2 h and calcium oxide (CaO) catalyst characterizations were carried out by X-ray diffraction (XRD), X-ray fluorescence (XRF), scanning electron microscope (SEM), and the Brunauer-Emmett-Teller (BET) surface area measurements. The effects of reaction variables such as reaction time, microwave power, methanol/oil molar ratio, and catalyst loading on the yield of biodiesel were investigated. Reusability of waste shell catalyst was also examined. The results indicated that the economic and environmentally friendly catalysts derived from oyster and Pyramidella shells showed good reusability and had high potential to be used as biodiesel production catalysts under microwave-assisted transesterification of Jatropha curcas oil with methanol.